Katonai helyőrségek a "Vajdaságban" 1867-1918 - Suba, János (Közép-Európai Közlemények, 2011)
This essay aims to present the military units that between 1867–1918 were supplied for by peace garrisons and supplementary units from Vojvodina, from the settlements of the area that today belongs to Serbia. Among the Imperial and Royal Troops (K. u. K.) the Regiments of Toot No. 86 from Szabadka, No. 23 from Zombor, and No. 6 from Újvidék (Novy Sad) were subordinated to the IVth Wing Headquarters of Budapest. Regiments of Foot No. 29 from Nagybecskerek, No. 43 from Fehértemplom were subordinated to the VIIth Wing Headquarters of Temesvár. Troopers Regiment No. 11 from Mitrovica was under the authority of the XIIIth Wing Headquarters of Zagreb in Croatia. As regards the Hungarian royal military units, Regiment of Foot No. 6 of Szabadka and the Battalion from Nagybecskerek of Regiment of Foot No. 5 of Szeged were allocated in the IInd Military District of Szeged. Units of the Regiment of Foot no. 7 from Versec were supplied from the Suthern parts of Temes county. Regiment No. 28 of Vinkovce were recruited from the townships of Szerém county.